Morphological Changes in Liver of Homeo- and Heterothermic Animals Under Artificial and Natural Hypometabolism - Lomako, Viktoriya V.; Shilo, Aleksandr V. (Problems of Cryobiology and Cryomedicine, 2017)
Morphological changes in liver of rats (Rattus norvegicus) and hamsters (Mesocricetus auratus) were studied under artificial (hypoxic-hypercapnic model) (AHM) and natural (hibernation) (NHM) hypometabolism and at the recovery stages (2 and 24 hrs after arousal). The following changes in liver morphology were observed: blood vessel hyperemia and blood thrombus formation (under AHM at all the stages in hamsters and 24 hrs after AHM in rats); the interstitial space expansion (in hamsters under AHM); hepatocytes with nuclei at different stages of necrobiosis (karyopyknosis, karyorrhexis and karyolysis) under NHM, in 2 and 24 hrs after AHM in both species; signs of protein dystrophies of various types and severity degrees (under NHM and AHM in hamsters, and 2 and 24 hrs after AHM in both species); tissue leukocyte infiltration (only in hamsters under AHM, NHM and 24 hrs after NHM); binuclear hepatocytes (in rats at AHM and 24 hrs later, in hamsters under NHM and 24 hrs later). The total protein content in liver was increased under AHM and 24 hrs after AHM in both species, as well as under NHM in hamsters. At these stages either the activation of degenerative and dystrophic processes (decomposition) or the appearance of binuclear hepatocytes (activation of protein synthesis) were observed. Probl Cryobiol Cryomed 2017; 27(2): 121-132